PEMAHAMAN DAN PERILAKU PENGGUNA JALAN TERKAIT DENGAN KONFLIK LALULINTAS DAN RISIKO KECELAKAAN - , RATIH LIBANIA, Prof. Dr. Ir. Siti Malkamah, M.Sc. ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Increasing the number of vehicles rapidly from year to year resulting traffic condition are getting worse like congestion and also potential for accident. Handling of transport safety problem consists of several components that influence each other, one of which was the behavior of motorists. Behavior of motorcyclists and private vehicles in each country is different, including in Indonesia. Behavior of motorists in Indonesia is unique, because the level of compliance and discipline are very low. This objective of this study is to know the description of user behavior motorcycles and private vehicles in Yogyakarta, and to know the understanding of the risk of accidents, and to know the level of safety as measured by traffic conflict involvement. Furthermore analyze the effect of an understanding of the risks of accidents on driving behavior and driving behavior to analyze the effect of traffic conflict involvement. Collecting data using a scale of driving behavior, a scale of understanding the risk of accidents and scale of involment conflict. Data were analyzed using regression analysis to determine the relationship between the understanding of the risk of accidents by driving behavior and driving behavior to the relationship between conflict involvement. The results showed that 52.67% rider has an understanding of the risk of an accident is low, it indicates that the security level riders tend to be low. 56.67% while the riders included in the category of low driving behavior and 54.67% motorists have the low conflict involvement as well. This shows there is an effort from the rider to improve road safety. Known that understanding of risk accident does not influence to driving behavior. While there is a positive correlation between driving behavior with the involvement of a conflict with rxy = 0.480 with the effective contribution of 23.1% driving behavior towards the involvement of the conflict. Behaviors that significantly influences to the conflict involvement are violations and errors.